2002
DOI: 10.1093/gerona/57.11.b379
|View full text |Cite
|
Sign up to set email alerts
|

Survival Characteristics and Age-Adjusted Disease Incidences in C57BL/6 Mice Fed a Commonly Used Cereal-Based Diet Modulated by Dietary Restriction

Abstract: Studies of C57BL/6 mice are often restricted to one sex, with limited characterization of pathology as a function of age. As part of the National Institute on Aging/National Center for Toxicological Research Collaboration on Biomarkers, over 3000 males and 1500 females of this strain were raised, maintained, and used to evaluate longevity under specific pathogen-free conditions. A diet commonly used in testing the impact of agents was fed ad libitum or was restricted to 60% of normal consumption, starting when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 46 publications
9
62
1
Order By: Relevance
“…Thus, the increased lifespan of Mclk1 +/2 could be the result of greater resistance to infectious microorganisms. Interestingly, in the survival experiment with Mclk1 +/2 mutants conducted previously in the background used in this study (C57BL/6J), we observed a surprisingly short lifespan for the control Mclk1 +/+ mice (20) compared with previously reported results for animals in this background (40,41). This suggests that environmental conditions, such as exposure to microorganisms, were limiting the survival of the wild-type animals in this particular experiment, yet Mclk1 +/2 mutants had significantly better survival than their Mclk1 +/+ siblings, possibly because of their hair-trigger immune response.…”
Section: Level Of Mitochondrial Changes Observed In Mclk1supporting
confidence: 70%
“…Thus, the increased lifespan of Mclk1 +/2 could be the result of greater resistance to infectious microorganisms. Interestingly, in the survival experiment with Mclk1 +/2 mutants conducted previously in the background used in this study (C57BL/6J), we observed a surprisingly short lifespan for the control Mclk1 +/+ mice (20) compared with previously reported results for animals in this background (40,41). This suggests that environmental conditions, such as exposure to microorganisms, were limiting the survival of the wild-type animals in this particular experiment, yet Mclk1 +/2 mutants had significantly better survival than their Mclk1 +/+ siblings, possibly because of their hair-trigger immune response.…”
Section: Level Of Mitochondrial Changes Observed In Mclk1supporting
confidence: 70%
“…We hypothesized that EpiSCs might differ from other somatic stem cells in their ability to resist aging because they must maintain complete integrity of the epidermal barrier for the lifetime of the mouse. Our results suggest that there is little, if any, loss in physiological capacity of murine EpiSCs over the lifetime of a mouse (Turturro et al, 2002).…”
Section: Discussionmentioning
confidence: 64%
“…B6 mice exhibit a completely different pattern of marrow and HSC aging than BALB mice; overall functional ability of marrow increases with age, and DR does not alter this effect (Figure 3). Although DR increases lifespan and decreases cancer in B6 mice, [19][20][21][22][23]25,26 DR probably fails to increase HSC functional ability in aged B6 donors because levels are already higher than that found in young controls (Figure 3). In the F1, functional ability of marrow also increases with age and is not altered by DR (Figure 4), suggesting that this B6 phenotype is genetically dominant.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Dietary restriction (DR) appears to break this paradigm. It is well known that DR decreases incidences of murine cancer with age, [19][20][21] counteracts most aging processes, and extends maximal lifespan in rodents. [22][23][24][25][26] Initial work in BALB mice showed that DR prevents both the loss of HSC clonal stability and the loss of BMC functional abilities with age.…”
Section: Introductionmentioning
confidence: 99%